Implementasi Sistem Aplikasi Pembayaran Digital Payment Dalam Pelaksanaan Pembayaran Berbasis Cashless Di Masa Pandemi Covid-19 - Wahyudi, Rama; Muhartono, Djoko Siswanto (Irpia : Jurnal Ilmiah Riset dan Pengembangan, 2024)
In line with the increasing trend of state spending payments, the government uses a digital system to implement cashless payments. The digital system provides benefits in the effectiveness of state spending payments to the recipient of the payment and supports the efficiency of state financial management. One of the digital systems used is the Digital Payment application developed by the Directorate General of Treasury. This study aims to review the use of the Digital Payment application in making non-cash payments to recipients of payments (suppliers) in the period 2019-2021. This study uses a qualitative method with literature study techniques and interviews with several sources. The results of this study indicate that the use of Digital Payment in non-cash payments is quite effective. However, there are still obstacles in system flexibility, mindset, and human resources so that the application has not been implemented optimally. To increase use, improvements to the Digipay application and ongoing socialization to MSMEs and expenditure treasurers are needed.